Opaganib in Coronavirus Disease 2019 Pneumonia: Results of a Randomized, Placebo-Controlled Phase 2a Trial. (11th May 2022) - Winthrop, Kevin L; Skolnick, Alan W; Rafiq, Adnan M; Beegle, Scott H; Suszanski, Julian; Koehne, Guenther; Barnett-Griness, Ofra; Bibliowicz, Aida; Fathi, Reza; Anderson, Patricia; Raday, Gilead; Eagle, Gina; et al.
Abstract: Background: Opaganib, an oral sphingosine kinase-2 inhibitor with antiviral and anti-inflammatory properties, was shown to inhibit severe acute respiratory syndrome coronavirus 2 replication in vitro. We thus considered that opaganib could be beneficial for moderate to severe coronavirus disease 2019 (COVID-19) pneumonia. The objective of the study was to evaluate the safety of opaganib and its effect on supplemental oxygen requirements and time to hospital discharge in COVID-19 pneumonia hospitalized patients requiring supplemental oxygen. Methods: This Phase 2a, randomized, double-blind, placebo-controlled study was conducted between July and December 2020 in 8 sites in the United States. Forty-two enrolled patients received opaganib (n = 23) or placebo (n = 19) added to standard of care for up to 14 days and were followed up for 28 days after their last dose of opaganib/placebo. Results: There were no safety concerns arising in this study. The incidence of ≥Grade 3 treatment-emergent adverse events was 17.4% and 33.3% in the opaganib and placebo groups, respectively. Three deaths occurred in each group. A numerical advantage for opaganib over placebo was observed in in this nonpowered study reflected by total supplemental oxygen requirement from baseline to Day 14, the requirement for supplemental oxygen for at least 24 hours by Day 14, and hospital discharge. Conclusions: In this proof-of-concept study, hypoxic, hospitalized patients receiving oral opaganib had a similar safety profile to placebo-treated patients, with preliminary evidence of benefit for opaganib as measured by supplementary oxygen requirement and earlier hospital discharge. These findings support further evaluation of opaganib in this population. Abstract : Upon receiving opaganib, patients with COVID-19 pneumonia who were hospitalized and required supplemental oxygen demonstrated good safety with no new concerns as well as potential symptomatic clinical improvement compared with placebo, with less supplemental oxygen requirement and earlier hospital discharge.